Temporal Profile of Brain Gene Expression After Prey Catching Conditioning in an Anuran Amphibian - Lewis, Vern; Laberge, Frédéric; Heyland, Andreas (Frontiers in Neuroscience, 2020)
A key goal in modern neurobiology is to understand the mechanisms underlying learning and memory. To that end, it is essential to identify the patterns of gene expression and the temporal sequence of molecular events associated with learning and memory processes. It is also important to ascertain if and how these molecular events vary between organisms. In vertebrates, learning and memory processes are characterized by distinct phases of molecular activity involving gene transcription, structural change, and long-term maintenance of such structural change in the nervous system. Utilizing next generation sequencing techniques, we profiled the temporal expression patterns of learning and memory-related genes in the brain of the fire-bellied toad, Bombina orientalis. The fire-bellied toad is a basal tetrapod whose neural architecture and molecular pathways may help us understand the ancestral state of learning and memory mechanisms in tetrapods. Differential gene expression following a prey catching conditioning event revealed activity in molecular pathways related to immediate early genes (IEG), cytoskeletal modification, axon guidance activity, and apoptotic processes. Conditioning induced early IEG activity coinciding with transcriptional activity and neuron structural modification, followed by axon guidance and cell adhesion activity, and late neuronal pruning. While some of these gene expression patterns are similar to those found in mammals, some interesting divergent expression profiles were seen, and differential expression of some well-known learning-related mammalian genes is missing altogether. These results highlight the importance of using a comparative approach in the study of the mechanisms of leaning and memory and provide molecular resources for a novel basal vertebrate model in the relatively poorly studied Amphibia.